2013
DOI: 10.3390/ijms141223471
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of mRNA Ventricular PRNP Prion Protein Gene Expression in Air Pollution Highly Exposed Young Urbanites: Endoplasmic Reticulum Stress, Glucose Regulated Protein 78, and Nanosized Particles

Abstract: Mexico City Metropolitan Area children and young adults exposed to high concentrations of air pollutants including fine and ultrafine particulate matter (PM) vs. clean air controls, exhibit myocardial inflammation and inflammasome activation with a differential right and left ventricular expression of key inflammatory genes and inflammasomes. We investigated the mRNA expression levels of the prion protein gene PRNP, which plays an important role in the protection against oxidative stress and metal toxicity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…To determine the mRNA expression of PrP C and GRP78, total RNA was extracted from the 72 heart samples using Trizol Reagent (InVitrogen Corp) (Villarreal-Calderon et al, 2013).…”
Section: Estimation Of Mrna Abundance Of Prp C and Glucose-regulated mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the mRNA expression of PrP C and GRP78, total RNA was extracted from the 72 heart samples using Trizol Reagent (InVitrogen Corp) (Villarreal-Calderon et al, 2013).…”
Section: Estimation Of Mrna Abundance Of Prp C and Glucose-regulated mentioning
confidence: 99%
“…The roadside Fe-rich NPs exhibit primary particle sizes ranging from < 10 to > 100 nm (Sanderson et al, 2016). These Fe-rich, traffic-derived CFDNPs display a range of undesirable characteristics including surface charge, high redox activity, association with transition metals and carcinogenic organic compounds, and strongly magnetic behavior, all likely to activate critical pathways for cellular and organ damage, including the heart and brain (Maher et al, 2016;Villarreal-Calderon et al, 2012a,2013 Calderón- Garcidueñas et al, 2018). Our previous studies have identified magnetic CFDNPs in the brains of Metropolitan Mexico City (MMC) residents of all ages (Maher et al, 2016) concomitant with Alzheimer's pathology starting at age 11 months (Calderón- Garcidueñas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, chronic and acute increases in myocardial mitochondrial ROS production can lead to a catastrophic cycle of mitochondrial DNA damage, functional decline, and further oxygen radical generation (Manickam et al, 2017;Nemmar et al, 2016;Tsutsui et al, 2006). Resultant cellular injury can include myocyte hypertrophy, endothelial dysfunction, apoptosis, and thrombosis (Tsutsui et al, 2006), and progressive modification of myocardial gene responses to oxidative and endoplasmic reticulum stress (Manickam et al, 2017;Villarreal-Calderon et al, 2013). Thus, irondriven myocardial mitochondrial dysfunction and uncontrolled ROS production can play a major role in initiation and progression of cardiovascular disease.…”
Section: Impacts Of Iron Overload In Mitochondriamentioning
confidence: 99%
“…Epidemiological studies reported that particulate air pollution not only has impact on the respiratory tract, but it has systemic and cardiovascular effects as well [1][2][3]. Acute exposure to particulate air pollution has been linked to a range of adverse cardiovascular events including hospital admissions with angina, myocardial infarction, and heart failure [4,5].…”
Section: Introductionmentioning
confidence: 99%